RISK MANAGEMENT AND EVALUATION AND QUALITATIVE METHOD WITHIN THE PROJECTS - IACOB, Vlăduț-Severian (Ecoforum Journal, 2014)
Making any project requires consideration of risks that may occur during the life of it. Therefore management of risk situations / difficult can be considered as a fundamental component of project management. The contents of this study will consider the highlighting in a theoretical form of the main aspects of risk and its management. It will also bring into question the use of qualitative risk analysis with examples on the probability - impact matrix.